2012
DOI: 10.1038/bjc.2012.375
|View full text |Cite
|
Sign up to set email alerts
|

Segmental chromosomal alterations have prognostic impact in neuroblastoma: a report from the INRG project

Abstract: Background:In the INRG dataset, the hypothesis that any segmental chromosomal alteration might be of prognostic impact in neuroblastoma without MYCN amplification (MNA) was tested.Methods:The presence of any segmental chromosomal alteration (chromosome 1p deletion, 11q deletion and/or chromosome 17q gain) defined a segmental genomic profile. Only tumours with a confirmed unaltered status for all three chromosome arms were considered as having no segmental chromosomal alterations.Results:Among the 8800 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 24 publications
5
135
0
6
Order By: Relevance
“…We evaluated each of these variables separately and also created a pooled variable reflecting the presence of segmental chromosomal aberration if at least one of these aberrations was present. 13 Clinical and biologic features were compared between groups defined by primary tumor site using 2 tests (for categorical variables) or t test or analysis of variance between groups (for continuous variables). We fit logistic regression models to describe the odds of having MYCN amplification according to primary tumor site after controlling for key potential confounders.…”
Section: ‫ء‬mentioning
confidence: 99%
“…We evaluated each of these variables separately and also created a pooled variable reflecting the presence of segmental chromosomal aberration if at least one of these aberrations was present. 13 Clinical and biologic features were compared between groups defined by primary tumor site using 2 tests (for categorical variables) or t test or analysis of variance between groups (for continuous variables). We fit logistic regression models to describe the odds of having MYCN amplification according to primary tumor site after controlling for key potential confounders.…”
Section: ‫ء‬mentioning
confidence: 99%
“…11,12). This implies that segmental alterations could represent either an intact NHEJ mechanism processing abnormally high numbers of DSB or an underlying abnormality of DNA repair and maintenance (13).…”
Section: Introductionmentioning
confidence: 99%
“…This abnormality is associated with poor prognosis, and is frequently coexisted with other biomarkers of aggressive disease such as MYCN amplification, older age, and chromosome 1p36 deletion. Loss of 1p36 region occurs in approximately a quarter of NB tumors and also predicted adverse outcome [2,3,7,11,13]. In addition, a recent INRG report on non-MYCN amplified tumors determined that it is not single genetic markers, but the overall segmental genomic profile of tumors that adds information to patient prognosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…Aggressive metastatic tumors are characterized by a high number of SCAs and a low number of Numerical Changes (NCAs). On the whole, genome-wide studies have demonstrated that critical chromosomal damages occur more frequently in older patients and that SCAs accumulate in an age-dependent manner, as supported by Schleiermacher and Coco [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%